2021
DOI: 10.18608/jla.2021.7113
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Sensemaking: Understanding How K–12 Teachers and Coaches React to Visual Analytics

Abstract: With the spread of learning analytics (LA) dashboards in K--12 schools, educators are increasingly expected to make sense of data to inform instruction. However, numerous features of school settings, such as specialized vantage points of educators, may lead to different ways of looking at data. This observation motivates the need to carefully observe and account for the ways data sensemaking occurs, and how it may differ across K--12 professional roles. Our mixed-methods study reports on interviews and think-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Similarly, Campos et al (2021) found that emotional, analytical, and intentional responses inform teachers' sense-making of the dashboard. In this light, teachers will respond differently to data visualization in the dashboard based on the different roles they play in schools.…”
Section: Teachersmentioning
confidence: 95%
“…Similarly, Campos et al (2021) found that emotional, analytical, and intentional responses inform teachers' sense-making of the dashboard. In this light, teachers will respond differently to data visualization in the dashboard based on the different roles they play in schools.…”
Section: Teachersmentioning
confidence: 95%
“…Using a think‐aloud protocol, teachers reviewed student results and feedback provided on the RISE dashboard, interpreted what they saw, and customized class lesson plans for the next day (as they saw fit). Prior research has noted the benefits of think‐aloud protocols on tasks involving building interpretations (Charters, 2003), including providing a low‐entry barrier (Campos et al, 2021) and tracing users' thinking (Liu & Stasko, 2010). To obtain verbalizations that accurately reflected the cognitive processes teachers implemented during responsive teaching, we refrained from providing detailed instructions or interpretation of results.…”
Section: Design Narratives In Co‐designing a Teacher Toolmentioning
confidence: 99%
“…It is also important to understand how teachers use interpretations of the learning analytics to adapt their pedagogical approaches (Campos et al, 2021). We hypothesize that this requires earlier engagement in responsive practices with teachers and coming to a shared understanding about the data they need to understand students open‐ended PBL strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The sensemaking framework of instructor analytics using dashboards elaborated in [33] starts by identifying the educational questions that lead to investigation and interpretation of the dashboard, followed by pedagogical responses. The process model for LA sensemaking through dashboards described in [6] evolves from one or more pedagogical events to its multiple data representations used by a set of sensemaking sub-processes (emotional, analytical, and intentional dimensions) to produce an interpretation of the events. The phases defined by these models are similar to the levels of situational awareness (SA) investigated by the naturalistic movement to explore human decisions [12]: perception of environmental elements in a volume of time and space, comprehension of their meaning, and projection of their state in the near future.…”
Section: Supporting Sensemaking With Ladsmentioning
confidence: 99%